Factors influence parents’ actions in providing advance measles immunization - Yuliantisari Retnaningsih; Nur Djanah (Poltekkes Kemenkes Yogyakarta, 2019)
Measles is a dangerous disease that is highly contagious through respiratory droplets. Measles can cause complications such as pneumococcal disease, diarrhea, meningitis. Measles immunization is one of the government's efforts to achieve the measles elimination target by 2020. High and even immunization coverage will form herd immunity and break the chain of measles transmission. The purpose of this study was to know the factors that influence parent's actions in providing immunization measles children in primary school. The research was conducted with a case-control design. The number of samples consisted of 104 case groups and 78 control groups of mothers who have primary school children in the area of ??Banguntapan Public Health Center, Bantul. Data collected with questionnaires analyzed with Chi-Square and multivariate tests. Variables related to the provision of advanced measles immunization are education level (p-value = 0.03), work status (p-value = 0.01), level of knowledge (p-value = 0.01), family support (p-value = 0, 01) and support of health workers (p-value = 0.01) Whereas unrelated variables are attitude (p-value = 0.17) and the reach of health facilities (p-value = 1.00).The variable that most influences the actions of the parent’s in giving advanced immunization against measles are family support with OR = 15,458. Related factors are the level of education, work status, level of knowledge, family support, and support of health workers. The most influential factor in the actions of parents in providing continued immunization against measles was family support.